Konservasi Sumber Air dan Wisata Edukasi di Desa Ngenep, Kecamatan Karangploso, Kabupaten Malang - Wahyu Prihanta; Elly Purwanti; Ach. Muhib Zainuri (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2022)
Desa Ngenep, Karangploso-Malang memiliki potensi sumber daya alam berupa sumber air, dinamakan Sumber Nyolo. Sumber Nyolo digunakan masyarakat untuk kebutuhan sehari-hari dan untuk pengairan lahan pertanian. Selain penggunaan untuk kebutuhan sehari-hari dan pengairan, saat ini kawasan Sumber Nyolo mulai dikembangkan menjadi destinasi wisata, yang dilakukan oleh kelompok masyarakat (Pokdarwis Sumber Nyolo). Pola pengelolaan yang dilakukan Pokdarwis masih tergolong sederhana, selain itu kualitas pengunjungpun beragam. Hal tersebut mempengaruhi kualitas sumber daya alam maupun kebersihan kawasan. Permasalahan pada kawasan Sumbernyolo, Desa Ngenep, Karangploso-Malang mendesak untuk dicari solusinya. Setelah sosialisasi, diikuti dengan meningkatkan sarana prasarana wisata dan elemen pendukung seperti pemberdayaan masyarakat sekitar. Keseluruhan proses akan selalu dimonitor dan dievaluasi secara berkala. Hasil kegiatan yang dilakukan terdiri dari dua aspek yaitu konservasi sumber air dan hutan dan pembangunan sarana wisata edukasi. Kesimpulan dari kegiatan ini adalah terbentuknya arah pengembangan wisata sumber nyolo menuju wisata konservasi dan kawasan wisata edukasi. Water Source Conservation and Educational Tourism in Ngenep Village, Karangploso District, Malang Regency Ngenep Village, Karangploso-Malang has potential natural resources in the form of water sources, called Sumber Nyolo. The Nyolo source is used by the community for daily needs and for irrigating agricultural land. In addition to use for daily needs and irrigation, currently the Sumber Nyolo area is starting to be developed into a tourist destination, which is carried out by community groups (Pokdarwis Sumber Nyolo). The management pattern carried out by Pokdarwis is still relatively simple, besides that the quality of visitors varies. This affects the quality of natural resources and the cleanliness of the area. Problems in the Sumbernyolo area, Ngenep Village, Karangploso-Malang urgently need a solution. The purpose of this service is to analyze the direction of developing Nyolo source tourism towards conservation tourism and educational tourism areas. The method of activity is carried out through the process of inventorying tourism potential, then developing a strategy for developing tourist destinations. For further socialization to the main actors of tourism, namely Pokdarwis and the surrounding community who are involved about the direction of development of Sumbernyolo tourism. After socialization, it was followed by improving tourism infrastructure and supporting elements such as empowering the surrounding community. The whole process will always be monitored and evaluated on a regular basis. The results of the activities carried out consist of two aspects, namely the conservation of water sources and forests and the development of educational tourism facilities. The conclusion of this activity is the formation of a direction for developing Nyolo source tourism towards conservation tourism and educational tourism areas.